STRATEGI PEMBELAJARAN TERDIFERENSIASI UNTUK SISWA SLOW LEARNER DALAM SETTING PENDIDIKAN INKLUSI - Yuni Ma’idah; Setianingsih; Ratna Ekawati; Slamet Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is driven by the need for instructional approaches that accommodate diverse student abilities in inclusive classrooms, particularly for slow learners. The research aims to describe the implementation of differentiated instruction strategies and analyze supporting factors, challenges, and their impact on the academic and socio-emotional development of slow learners at SDN Dermo 1 Bangil. A qualitative case study design was employed, with data collected through observation, interviews, and documentation, and analyzed thematically. The findings reveal that differentiation in content, process, and product enhances active participation, self-confidence, and learning outcomes among slow learners. Teachers play a crucial role in adapting instructional strategies based on students’ readiness and learning styles. This study contributes theoretically to strengthening adaptive learning practices in inclusive education and offers practical recommendations for teachers to create responsive and equitable learning environments that support individual learning needs.